Monitoring of the center of pressure in unipedal support in karate - Benosmane, A. B. (Journal of Sport Science Technology and Physical Activities, 2021)
Stabilometry is a technique for analyzing posture based on recording the oscillations of a subject's center of pressure (COP) on an instrumented platform. Under unusual or destabilizing conditions, maintaining postural activity requires the establishment of rapid motor reactions. In this context, we proposed to do the biomechanical monitoring of the stability of two elite karate athletes of different specialties during the execution of an attacking movement of the foot. The analysis carried out on the evaluation of the equilibrium capacity by stabilometric measurements showed different trends in the evolution of the COP. This work could find many applications for the study of behavioral changes occurring with age, both for the detection of young talent and for the monitoring of seniors.